A STUDY OF ADJUSTMENT OF STUDENTS STUDYING IN SECONDARY SCHOOLS OF BAREILLY DISTRICT - Tripathi, Neetika; Pandey, Mahendra Prasad (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This research aims to explore the adjustment challenges faced by secondary school students in the Bareilly District. Adjustment is an ongoing process through which individuals adapt to their environment, maintaining a balanced and dynamic personality. It plays a pivotal role in various aspects of a student's life, influencing their overall well-being. The focus of this study is to evaluate students' adjustment levels in five key domains: home, health, social, emotional, and educational. A sample of 200 students from different degree colleges in Jammu city was selected for this study. The research tool used was the Adjustment Inventory for Secondary School Students, standardized by A.K.P. Sinha and R.P. Singh (2012). Data collected from the participants were analyzed using statistical methods such as mean, standard deviation, and critical ratio. The results indicated a significant difference in adjustment levels between male and female students, with male students showing better adjustment in all five areas.